Learning to Read the Qur'an Using Small Application-Based Learning Media for Grade 6 Students of SDN 1 Kedungdawa, Gabuswetan District, Indramayu Regency - Lutfiah (Konsultan Jurnal Ilmiah Indonesia, 2024)
In the world of education, many applications have been developed that help humans gain knowledge such as ebooks, educational games and learning applications. These applications are utilized and continue to be developed. The majority of Indonesian people are Muslim. Reciting the Koran should not only be studied at TPQ or schools but also needs to be studied at all times. This is because today's knowledge is not limited by time. Difficulties in pronouncing the hijaiyah letters and tajwid are not only experienced by children but also adults. With the development of existing technology, it can make it easier to learn from an early age, namely with the Koran learning application. In addition, the use of applications or software that support learning is still rarely introduced to students. The implementation of this activity aims to help students in the field of technology or IT to facilitate homework (PR) given by teachers, especially in the field of religious studies. The methods used during learning assistance are lectures, discussions and practices. The lecture method is used during the introduction of the Reciting Application and its use. Data collection uses pretest and posttest questions and the results of data collection are analyzed using exams to determine the increase in results while students are participating in learning assistance. Based on the implementation of the activity, the results of this activity are, students who follow the program are very enthusiastic and are expected to continue when outside of school to minimize playing less educational game applications.